Short-term effects of thinning on the growth and soil improvement of typical stands in the Yellow River Delta - Liu, Wenjing; Wang, Lichao; Xia, Jiangbao; Lu, Yue; Zong, Xianguo (Frontiers in Microbiology, 2025)
The effects of thinning were studied on stand growth and the physicochemical soil characteristics of typical plantations in the Yellow River flood plain in northern Shandong Province. Growth indices and soil physical and chemical indices were monitored and in 8-year-old plantations of Fraxinus chinensis, Salix matsudana, and Ulmus pumila in the Yellow River Delta. Data were collected at an initial stand density of 3 m × 3 m and 3 years after artificial thinning to a stand density of 3 m × 6 m. (1) Thinning promoted growth, and the effect on the U. pumila plantation was the greatest. The diameter at breast height, tree height and crown width increased by 41.28, 19.98, and 59.49%, respectively. (2) Thinning increased the soil moisture at the studied plantations, reduced the soil bulk density, and increased the soil porosity and the water holding capacity. The results differed among the plantations, with the greatest improvement occurring at the U. pumila plantation. (3) Thinning had a greater effect on inorganic than on organic soil nutrients according to forest type; the changes in nitrogen, phosphorus and potassium contents in different soil layers substantially varied with the species planted. Most variables significantly differed at the S. matsudana plantation, and the changes in different soil layers were inconsistent. (4) Thinning significantly increased the correlations between stand growth and soil physicochemical properties. Thinning positively affected forest growth and soil physicochemical properties, but the variation in each index across the different plantations was quite different. Thus, thinning could help promote the stable and sustainable development of forest plantations in the Yellow River Delta, and these results provide a reference for the rational management of plantations.